Breed preference and breeding practices for goats in agro-pastoral communities of semi-arid and sub-humid areas in Tanzania - Chenyambuga, S.W.; Lekule, F.P. (2014)
A study was carried out to determine farmers’ preferences for goat breeds, desired traits, management and breeding practices in agro-pastoral communities of central and eastern Tanzania. A total of 552 goat keepers from semi-arid and sub-humid areas were involved. Information on goat flock size, breed preferences, breeding practices, traits preferred and husbandry practices was collected using a well structured questionnaire. Out of the 552 household heads, only 21.3% were women. Most of the farmers kept indigenous goats belonging to the Small East African breed and the mean number of goats per household was 8.9 ± 1.0. The majority of the farmers (53.4%) preferred to keep the Small East African goat breed rather than the exotic breeds. The Small East African breed was preferred to exotic breeds because the animals are easier to feed, prolific, tolerant to drought and endemic diseases. Most farmers (70.8%) practiced uncontrolled mating using bucks from either their own flock (66.7%) or neighbours’ flocks (33.3%).Uncontrolled mating was preferred because it is easier to practice (41.2%) and cheaper (41.2%). The buck to doe ratio was 1:3 in semi-arid and 1:2 in sub-humid areas. Breeding males were selected based on body size by the majority (85%) of the goat farmers. It is concluded that livestock keepers in semi-arid and sub-humid areas in Tanzania prefer the Small East Africa goats because the animals are abundantly available and well adapted to the local environmental conditions.